Pierre Floquet - What is (not) so French in Les Triplettes de Belleville - Timo Linsenmaier (Animation Journal, 2006)
In an article on text theory, Roland Barthes wrote: “Every text is intertext; it holds other texts within, at various levels, in irregularly recognizable shapes: those of the preceding culture as well as those of the surrounding culture; every text is new with interwoven past quotations”1. A text, a film, or an animated film is built and framed with a mosaic of quotations that work together into an original feature. It absorbs, transforms, and makes its own textform. These quotations may be considered as references, whether they be textual, filmic, and/or cultural. However, references may limit their meanings to comments within, and aside of, a discourse, whereas intertext implies that such elements are integrated into the diegesis. A reference is intertext when it actually takes part in the plot, and conveys a meaning of its own. As we shall see, Les Triplettes de Belleville abides by such a narrative approach. As a Frenchman, I am aware that many elements in the film cannot be appreciated and assessed similarly by those unfamiliar with French culture. This paper offers non-French audience clues to the intertext of the film, including universal themes that reach across cultures. <!–more–> Director Sylvain Chomet himself, mentioning the diegetic time of his story (the 1950s), specified: “I was a kid at that time, so of course I am nostalgic of my childhood - but who would not be?! […] However, it would be wrong to believe things were better off in those days; I would rather say the contrary.”2 Many critics in France and abroad have enhanced the nostalgia in Les Triplettes de Belleville. To me, this is the case in point: how can one be nostalgic of a period that is not considered regrettable? So, what is there beneath such apparent nostalgia? Nostalgia of good old France does not systematically appeal to foreigners; so why has Les Triplettes de Belleville been so successful abroad? First, I will develop and explore some of the clichés that feature in the film, and mainly speak to the French. Then, we shall see how, while crossing the Atlantic Ocean, plot, characters, and audience are given distance, whether it be geographic or humoristic. Such distance enables a different insight into the meaning of the film. The French Perspective Les Triplettes de Belleville is filled with clichés reflecting a French perspective. One such cliché is that Americans are obese. Chomet seems to have this stereotype in mind, as he repeats in Les Triplettes de Belleville the same description of fat Americans as the caricature of tourists in Paris found in his first, celebrated short La vieille dame et les pigeons (The Old Lady and the Pigeons, 1998). In this film, the typically cliché-esque tourists are featured in both the opening and ending sequences, as punctuations of a story that just happens to take place in Paris. Their debatable manners work as a reflexive counterpart to the eccentric neurotic behaviours of both the policeman and the old lady. They are ridiculed, each one of them, either tourist or citizen, in their own ways, and beyond the scope of their apparent differences — so obese Americans in Chomet’s films are not necessarily illustrative, they are factual components among others of a parodic world. If the tone of the film sounds anti-American, it is less Chomet’s own ideas than his will to mock the point of view of ‘Mr. Average Frenchman’. Basic anti-American prejudice goes on with “Hollyfood” and a voluptuous overweight Statue of Liberty holding a hamburger, which relates to “mal bouffe”3, something like “ill grub”. (In France, McDonald’s is the evil symbol of “mal bouffe”). Bill Plympton, in a bonus section of the DVD, discusses release plans for the United States, arguing that US viewers should be allowed to laugh at themselves and that they can handle jokes about (fat) Americans. (Remember the image of the man with Mickey Mouse and a “sucker”!) The best comedy is rooted in the truth, and, as we shall see, the French are targets as well. Of course obesity is not specific to US citizens. Apart from the fact that today 12% of French people are overweight, at the time of the story, Albert Dubout (1905 – 1976) was very famous for his caricatures of huge wives choking their tiny husbands under their fat and authority. The early sequence of Les Triplettes de Belleville, displaying a mock red-carpet ceremonial, is a direct tribute to these famous ill-matched French couples. Repeating Dubout’s caricatures, Chomet obviously celebrates his art, and reactivates the acid criticism aimed at the bourgeoisie. Still, at that time, as in the past centuries, working class people could not afford to become obese. On the contrary, being fat was a sign of good health and wealth! There are many other references in the film that function as elements of cultural intertext that a non-French viewer may easily catch, from Chaplin and Tati’s films to Winsor McCay and Fleischer cartoons; from Glenn Gould and Django Reinhardt to Fred Astaire. Also included is Josephine Baker, a black American entertainer who emigrated to France in the 1920s to escape racism, and became famous before WWII with her songs and semi-nude shows in cabarets. However, there are other references that are perhaps less conspicuous to foreigners, such as the 1960’s clock on TV, the “Parisien Enchaîné” (a humorous reference to two existing papers, Le Parisien and Le Canard Enchaîné), and the hint to Vache qui rit cheese. The high bridge that pushes Mme Souza’s house into a tilt is typical of railway constructions in France during the first half of the 20th century. If you commute by train from Orly airport to Paris, you will actually travel past similar sites. A more exclusive reference is found in the receptionist at the French Mafia Wine Center, who bears some verisimilitude with José Bové4, a left wing anti-globalisation activist. With a beret, moustache and taste for red wine, the French mafia Godfather is a reminder of one famous character by Gotlib, a French cartoon artist of the late XXth century: Super Dupont (a possible translation: Super Smith), some unlikely son of Superman and Mr. Average Frenchman, who would appear in Les Triplettes de Belleville in his drunkard version. Isn’t the mafia’s moto “In vino veritas”, acknowledging the fact that the French adore nothing but wine?! The hit-men, here again, are the monstrous genetic clones of Men in Black, Inspector Cluzot, and J.M. Folon’s flying men. In the thrilling car-chase, which reminds us of Bullit’s (1968) sequence in the streets of San Francisco, the hit-men drive customized 2CVs5. The old popular car is yet another cliché in France, as much as it has turned into a myth. Choosing such a car for the chase sequence stands as a distorted allusion to the ever more speedy, improbable car-chases that fill the screens today. In France and Europe, the 2CV has the same level of fame as the Model T Ford in the United States, though it probably had a lesser impact on car industry. A very slow, thin bodywork, soft top vehicle, it was designed at the outbreak of WW II and put into production in the late 1940s, and was meant to be able to safely carry a basket of eggs across a freshly ploughed field. It quickly became a very popular car, and then a student car in the 1960s onward. The 2CV reached filmic fame in yellow paint with James Bond in For Your Eyes Only (1981). Though it appeared in many other films, most notable was George Lucas’ American Graffiti, in 1973, as Curt’s symbol of non-conformism, and more recently in Indecent Proposal (1992). Today the 2CV is turning into a collector’s item. Huge rallies regularly occur in Europe, and people turn up with modified, customized 2CVs. The long bonnet model is a favourite, and a joke as its engine is only 400cc! Of course, Chomet’s using them in a car-chase is comic absurdity turned surrealistic. The Tour de France is the last cliché to be considered here. This major sport event stands as a symbol of deep France summer vacation entertainment. Over 100 years old, it embodies what the “français moyens”, or French working class, may be. In the film, these individuals are the first to be celebrated and acutely parodied, far before the fat Americans. The cycling and Tour de France related sequences are peak periods of the filmic time spent poking fun at typical aspects of the French working class. I believe that the Tour de France has become more popular in the United States thanks to men like Lance Armstrong, and many race images are widely familiar. The mountain legs are moments of many legendary struggles among riding stars. At an early stage in the film, one can see a poster of Fausto Coppi, an Italian champion. Some of the most famous cyclists at the time of the story were Raymond Poulidor (mentioned as Poupou in a mock De Gaulle speech in the film), who always finished second to Jacques Anquetil (a five-time winner). The yellow jersey, the leader of the race, shown in the film is the caricature of Anquetil. Chomet introduces such revered moments in the history of the Tour de France, reactivates its codified dramaturgy (such as the long wait before the pack rides past in a few seconds), and draws some scenes that directly appeal to the French collective memory. The racers are always preceded by the “caravane”, and its wake of promotion and entertainment motorized ventures. In the film, "Roberte Rivette", the accordionist who plays her instrument atop a truck while following the cyclists, represents Yvette Horner, a once highly popular artist who not so long ago still played her accordion to large crowds in France. She always has been caricatured with her broad ever-lasting smile that shows big teeth. Horner recently described her own experiences as very similar to those of "Roberte Rivette" in Les Triplettes de Belleville: she continued playing her accordion along the Tour de France route with a big smile as insects ceaselessly were caught in her teeth. The race is followed by the “voiture-balais”, literally the “broom car”, depicted in the film as a vintage Citroen van, and a major element in the kidnapping of Champion. Whether actively practicing, or simply relishing watching races, the French love cycling; and maybe Americans love to watch them loving it? The point is, the parody can be enjoyed differently. The yellow jersey, the mafia Godfather, and Roberte Rivette are cliché-esque characters who reflect Chomet’s appeal toward the French working class of that time, but non-French spectators may perceive them as exotic and nicely “Old-World”. In any case, they remain secondary characters, and to some extent belong to the setting. As such they are mere foils to the main characters. When we first meet Champion, he is a podgy little boy. As time goes by, he turns into a tall, skinny, stooping man with a huge nose, and balloon-like thigh and calf muscles. He is fed like one would feed an animal. When kidnapped, whinnying and horse grunting sounds are part of the sound track. During the sequence in the boat hold, he actually has the appearance of a racing horse in his box. Chomet seems to make the young cyclist aloof, even from us. He is utterly self-absorbed and never unbends to offer thanks for his grandmother’s aid or even to acknowledge their attempt to escape. But would a racing horse express thanks? Is he still human? A young orphan turned into a cycling monster, he only rides his bike, lost in the effort. Bruno develops from a tiny puppy to overweight hound with a complacent and accepting nature. He is the character with whom the audience is meant to empathize. We are panting with him in eager anticipation as he waits for Champion to eat the required amount of dinner, so he can slurp up the rest. And when he collapses lovingly on Champion, we smile a sigh of relief. Bruno is gloriously canine. He dreams of the things that are important to him; he sees the world as smells and images. Characters in the film are grotesque and ugly, a very unusual feature for heroes and even villains—quite the opposite of the animations of Pixar and Disney. Madame Souza shares similar features to the dog and has a shorter leg. The gangsters are rectangular and their boss is very short. The Triplettes look like witches, yet obviously, their “ugliness” is just a matter of appearance. The Triplettes themselves are but the barely surviving shadows of their former glory, a trio of benevolent vaudeville artists, paradoxically stuck between the Three Fates and Macbeth’s witches. In any case, they bear some immaterial connection with the world beyond — beyond the ocean, they are Mme Souza’s guide into the surrealist universe of Belleville. Madame Souza recognizes that something is missing from Champion’s life. His parents are, clearly, gone. All he has left is a picture of them on a bicycle. Emotion is tangible, but remains as discreet as Mme Souza apparently is. As she is Portuguese, one may easily imagine she works somewhere as a cleaning lady in someone else’s home, as many female Portuguese immigrants did and still do in France. As she tenderly and silently pieces together what Champion needs to be happy, she and he discover a new life (a way out?) as participants in the Tour de France. Chomet invests feelings in Madame Souza through her expression — the simple dark circles of her eyes set behind thick lenses and the line of her mouth, which modulates between forthright resolve and a gentle satisfaction. Universal Themes Chomet sketches the human figure with loving detail of its imperfections, drawing together networks of strange and interesting looking faces before bringing them to life. Chomet’s portrait of the human race is bleak but forgiving, framed simultaneously with compassion and cynicism. There is a dark and disquieting grace in the way the story goes. So, beyond clichés and parody, it tells us of the power of one person's love and concern for another. If, quoting Tex Avery, “in a cartoon you can do anything,”6 Les Triplettes de Belleville tells us about unconditional love. Such considerations reach well beyond any narrow-minded nationalist perspective. Indeed, there, Chomet is talking about universal conditions. Or “showing”, I should say, as indeed there is hardly any talking in the film. More generally, drawings are telling the story, movements expressing both drama and pathos. Les Triplettes de Belleville creates a unique world, filled with images and sights we have never quite seen before. By eliminating speech as a means of storytelling, Chomet heightens the surrealistic tone of what is being shown on screen. He reinvents a ‘sign-language’ that knows no linguistic barrier. (Mme Souza’s eye movements are one telling example.) Yet, Les Triplettes de Belleville is by no means silent. In fact, sound is a critical element of the film, whether it is in the approach of a train, the croaking of frogs, or the barking of a dog. Though meaningful dialogue is minimal, onomatopoeias, sound-effects, and noise in general add to the notion of universality that emerges from the film, so much so that international versions need not be dubbed. One sequence actually highlights this feeling, conveyed by the whole film: when Mme Souza and the Triplettes meet by the fire, the hand clapping rhythm accompanied with the wheel originated sounds is the key to their relationship. The sound may well be primal, tribal, yet it enables them to communicate and understand each other; sound is universal. Names may also convey a similar, and humorous, meaning. The meaning may be more obscure; still, it plays with the same connotation, wittily applied to two cultures that suddenly become one. The barmaid’s name, for example, deserves closer analysis. She is called Fanny Roberts. Though “Fanny” may simply be a name in France, it means more in Shakespeare’s language, with subtle variations depending on which side of the Atlantic one stands! Similarly, “Robert” is a name in English, as it is in French. It also is French slang for breasts, something like “boobs”. Thus, in two words, Chomet ironically teaches us that triviality is cosmopolitan. The notion of universality extends to the context in which the action plays out. Champion and Mme Souza’s sea crossing is not innocent. Mozart’s Kerrie and the tempest turn it into some mystic, if not initiatory, crusade. It takes them away from the France we (all) know through its grotesque caricature, into some hysterical megalopolis of nightmarish shapes and dimensions. This no-where can in fact be perceived as anyone’s any-where - some urban, and dangerous, everyman’s land. Chomet plays with false clues and pseudo references. Belleville is actually both a working class suburb of Paris, and a Canadian town somewhere between Montréal and Toronto. In the film, following Mme Souza and Bruno, we cross the ocean, so we must be in North America. As we follow the ship, she enters a river inhabited by whales, recalling the St Lawrence, and see buildings could be Montréal’s. Moreover, Bruno steals a sausage from a beggar with a thick French Canadian accent. But we also get the Statue of Fatberty, suggesting that they are in New York. Its gothic architecture may also merge the cityscape into some even more generic location. However, this urban kaleidoscope could still be in France, or at least in Europe, if we consider the style of wall sockets for the vacuum cleaner and the road-signs. Going home onboard their improbable wheeling raft, our heroes cross a bridge that recalls at the same time New York and San Francisco. However, they do not cruise away: they vanish into the night. Thus, we are no longer tackling clichés to be spotted and laughed at, we are invited into one surrealistic universe that may mean and appeal to any of us. In their journey, apparently from one town to another and back (but are they really two different places?), the main characters experience an initiation, a quest into the inner meaning and values of human relationships. As Mme Souza and Champion depart, their opening to humanity is certainly wider. Yet, they disappear into the darkness onboard their shaky raft; their journey with the Triplettes- Three Fates may also symbolically suggest their awakening to and acceptance of death. The following sequence shows lonely old Champion deep into his memories: obviously Mme Souza has died, and the Triplettes are no longer in sight. Thus the mood of the film is decidedly rather grim. Its surrealistic dimension is not only conveyed by the plot and setting, but also by the subtext. The audience is not witnessing a tragedy, yet they are preserved from any closing comic twist or any light-hearted conclusion. Chomet does not indulge himself in suggesting the relief of a conventional Hollywood-typed happy end. Emotion is ripe, and connotes what may be perceived as a very existential questioning of the meaning of life. Chomet will not offer any clear answer; stepping away from nostalgia into the awareness of life and of its hardships, he sustains his film with disillusioned utopia. During the 1950s, Charles Trénet used to sing Douce France (Sweet Gentle France), and render an optimistic picture of what Chomet describes as finally rather bleak. Cultural references are multiple and intertext underlies the whole film; yet, its meaning goes beyond the sclerotic frame of cultural ghettoes. This is not the time, nor the place to pity oneself over some sick nostalgia. Chomet’s diegetic no-where, somewhat surrealistic and Bunuelian, works out as a cultural crossroad and it expresses a rather universal idea. Two illustrations of it: first, the scene of the grandmother at the start, giving the boy a bike and then hiding behind the door to see if he likes it, is touching, honest and vividly real. Second, the final sequence mirrors the opening one: Champion, grown old, looks away from the screen of his own story; he turns around, looking behind and symbolically back into the past for Mme Souza and his memories. His eyes are sad, tender, and weary, and remind us of Mme Souza’s as she would look upon him when a child orphan. What drives her throughout the story is the loving tenderness between an old lady and her grandson. Gone laughter, action, and surrealistic neo-urban settings! At the very end of the film, we are not left with nostalgia; we are filled with that lasting uneasy feeling, and a very commonly humane one, of loneliness and of love beyond the boundaries of death. Pierre FLOQUET teaches English, and is head of the language department, ENSEIRB, Bordeaux University. The paper was originally presented at the 18th Society for Animation Studies Conference in San Antonio, TX in July 2006. Notes 1 Roland Barthes (1973) "Texte (théorie du)", Encyclopaedia universalis: “Tout texte est un intertexte; d'autres textes sont présents en lui, à des niveaux variables, sous des formes plus ou moins reconnaissables: les textes de la culture antérieure et ceux de la culture environnante; tout texte est un tissu nouveau de citations révolues.” (My translation) 2 The interview with Chomet was accessed at this website: http://cinema.tiscali.fr/ficheart.aspx?keys=AR016890&file=http&type=art 3 “Bouffe” is slang for food, and in a large quantity. It connotes a lack of refinement, and is the opposite of gourmet food. “Bouffer” is slang for “to eat”; it also means “to puff “, “swollen”. So “bouffe” is easily related to obesity. “Mal” means both “bad” and “evil”. 4 Many thanks to Floriane Place-Verghnes for her clear-sightedness. Please refer to her paper : “Douce France? Les triplettes de Belleville, de Sylvain Chomet”, in: Pierre Floquet (Ed.). 2007. CinémAnimationS, Paris: Corlet. 5 “2CV” means “two horse power”, and corresponds to the actual power of the car engine. 6 Big Heel Watha, 1944. © Pierre Floquet, 2006 Edited by Nichola Dobson To download this article as PDF, click here.